Determination of immunophenotypic aberrancies provides better assessment of peripheral blood involvement by mycosis fungoides/Sézary syndrome than quantification of CD26− or CD7− CD4+ T‐cells. Issue 2 (15th July 2020) - Lyapichev, Kirill A.; Bah, Ismael; Huen, Auris; Duvic, Madeleine; Routbort, Mark J.; Wang, Wei; Jorgensen, Jeffrey L.; Medeiros, L. Jeffrey; Vega, Francisco; Craig, Fiona E.; Wang, Sa A.
Abstract: Background: Blood involvement by mycosis fungoides (MF)/Sézary syndrome (SS) influences prognosis and therapeutic decisions. MF/SS blood stage is currently determined by absolute CD4 + CD26− or CD4 + CD7‐cell counts, which quantification method may overestimate MF/SS by including CD26− or CD7− normal CD4+ T‐cells, or underestimate disease burden when MF/SS cells show incomplete loss of CD26 and/or CD7. Recently, through the standardization effort led by the International Clinical Cytometry Society (ICCS), recommendation was made to quantify MF/SS by enumerating immunophenotypically aberrant CD4+ T‐cells, rather than CD26− or CD7− in isolation. Methods: We compared these two quantitation methods in 309 MF/SS patients who had blood samples analyzed by flow cytometry immunophenotyping (FCI) over a 1‐year period. Results: Using the European Organization of Research and Treatment of Cancer (EORTC)/International Society for Cutaneous Lymphomas (ISCL) criteria, 221 (71.5%) patients had a blood stage corresponding to B0, 57 (18.4%) to B1, and 31 (10%) to B2. By FCI analysis, a total of 62 patients (20.0%) were found positive for MF/SS. Among EORTC B0 patients, 11/221 (5%) were positive by FCI (false negatives), and among EORTC Stage B1 patients, 35/57 (61%) were negative by FCI (false positives). Regarding patients positive for MF/SS cells by FCI, there was an overall excellent correlation ( r = .999, p < .001) between the EORTC/ISCL method and FCI method; however, four (6.5%) patients would have an altered B stage between B0 and B1. Conclusion: The MF/SS cell quantification method using immunophenotypic aberrancies, as recommended by the ICCS, allows to distinguish MF/SS cells from background benign T‐cells and enables for more accurate staging, especially among patients currently being considered to have B0 and B1 stage diseases.